Listeria Monocytogenes 2018
DOI: 10.5772/intechopen.76287
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Environmental Stresses in the Virulence Traits of Listeria monocytogenes Relevant to Food Safety

Abstract: Listeria monocytogenes is a foodborne pathogen, which causes listeriosis disease among humans and other animal species. Infections in humans mainly occur in immunocompromised individuals and are caused by the consumption of ready-to-eat and raw food products contaminated with the pathogen. To ensure survival in nature, L. monocytogenes easily adapts to different environmental conditions, and that justifies the hurdles to prevent bacterial growth inside the food chain. Exposure to a single or multiple sublethal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 102 publications
0
12
0
1
Order By: Relevance
“…It has exceptional physiological abilities to ensure its survival by adapting quickly and easily to harsh divergent physiological conditions [11]. Studies have shown that subjecting L. monocytogenes to food-related stresses including low storage (refrigeration) temperatures may induce increased expression levels of the organism's virulence genes, and thus increase the risk of listeriosis [12].…”
Section: Introductionmentioning
confidence: 99%
“…It has exceptional physiological abilities to ensure its survival by adapting quickly and easily to harsh divergent physiological conditions [11]. Studies have shown that subjecting L. monocytogenes to food-related stresses including low storage (refrigeration) temperatures may induce increased expression levels of the organism's virulence genes, and thus increase the risk of listeriosis [12].…”
Section: Introductionmentioning
confidence: 99%
“…monocytogenes is exposed to diverse stresses in FPEs and during infection. Refrigeration to preserve food products both in production facilities and in consumers' fridges imposes low temperatures, and oxidative stress is caused by sanitizer agents, especially disinfectant application and antibiotic treatments [5,6]. Disinfectants based on quaternary ammonium compounds are the most common bactericidal agents used in the food industry, and chlorine derivates or peracetic acid are also applied to prevent L. monocytogenes spread within facilities [7].…”
Section: Introductionmentioning
confidence: 99%
“…L. monocytogenes can sense stressful conditions through molecular signalling [10] and activates survival strategies to reduce oxidative damage; these strategies include expression of sigB, cold and heat shock proteins (cspABCD), proteases (clpC, clpP, groEL) and genes related to oxidative response notably superoxide dismutase (sod), perR and catalase (kat) [11][12][13]. sigB acts on genes related to stress (GRS) and virulence genes such as inlA and LIPI-1 [5]. L. monocytogenes virulence can increase under stress conditions: prf A is regulated by a sigB-depedent promoter, and clpC expression influences some genes responsible for adherence [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…is is of great concern because the tolerance to acid stress by pathogens aggravates their virulence [12,13].…”
Section: Introductionmentioning
confidence: 99%